Case Study Of E-Marketing On Online Social Networking Industry - Binti Ahamad, Sazlina (2011)
This paper discusses several popular social networking sites and their features and services. Firstly, it will explore the definitions of social networking sites and e-marketing, advantages and the challenges of SNS, then followed by discussing the critical success factors of SNS that have been identified from the literature review. This study aims to research on the credibility of the social networking industry in order to be an effective e-marketing tool. The findings of this study will help to devise strategies on how the websites could support e-marketers better. It also underlines the implementation planning, highlight the potential risks that social networking industry should mitigate and emphasizes on the opportunity of social networking industry to support e-marketing.